2012
DOI: 10.1371/journal.pone.0049557
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Release of Ventral Tegmental Acetylcholine and Accumbal Dopamine by Ghrelin in Rats

Abstract: Ghrelin, an orexigenic peptide, regulates energy balance specifically via hypothalamic circuits. Growing evidence suggest that ghrelin increases the incentive value of motivated behaviours via activation of the cholinergic-dopaminergic reward link. It encompasses the cholinergic afferent projection from the laterodorsal tegmental area (LDTg) to the dopaminergic cells of the ventral tegmental area (VTA) and the mesolimbic dopamine system projecting from the VTA to nucleus accumbens (N.Acc.). Ghrelin receptors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 71 publications
2
64
0
2
Order By: Relevance
“…However, this needs to be further elucidated. The findings that the cholinergic–dopaminergic reward link is activated by pharmacological‐induced hyperghrelinemia (Jerlhag, 2008; Jerlhag et al., 2012) and that elevated ghrelin levels associated with craving (Addolorato et al., 2006; Koopmann et al., 2012; Leggio et al., 2012), may imply that high plasma levels of ghrelin may be needed for reward interactions. Supportively, animal studies show that hyperghrelinemia is associated with cocaine seeking and that peripheral ghrelin administration augments the cocaine‐induced conditioned place preference and locomotor stimulation (Clifford et al., 2012; Davis et al., 2007; Tessari et al., 2007; Wellman et al., 2005, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, this needs to be further elucidated. The findings that the cholinergic–dopaminergic reward link is activated by pharmacological‐induced hyperghrelinemia (Jerlhag, 2008; Jerlhag et al., 2012) and that elevated ghrelin levels associated with craving (Addolorato et al., 2006; Koopmann et al., 2012; Leggio et al., 2012), may imply that high plasma levels of ghrelin may be needed for reward interactions. Supportively, animal studies show that hyperghrelinemia is associated with cocaine seeking and that peripheral ghrelin administration augments the cocaine‐induced conditioned place preference and locomotor stimulation (Clifford et al., 2012; Davis et al., 2007; Tessari et al., 2007; Wellman et al., 2005, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin also declines following two months of successful abstinence from nicotine (Lee, Joe et al 2006) but some have shown that ghrelin is not associated nicotine craving and withdrawal symptoms (Mutschler et al, 2012). In addition, ghrelin interacts with the nicotinic acetylcholine receptor to stimulate dopamine release in the brain, particularly in areas related to drug reward and emotional functioning (Jerlhag, Janson, Waters, & Engel, 2012; Palotai et al, 2013a, 2013b). An early genetic study has identified ghrelin genes and personality trait relationships that may have implications for trait differences between alcoholics and non-alcoholics (Landgren et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin increases dopamine receptor D5 and acetylcholine receptor nAChRβ2 gene expression in the VTA and decreases expression of dopamine receptor genes D1, D3 and D5 and acetylcholine receptor gene nAChRα3 in the nucleus accumbens 28 . Ghrelin increases ventral tegmental acetylcholine and increases dopamine release in the nucleus accumbens 57 . It is claimed that glutamate is required for ghrelin to stimulate the mesolimbic dopamine system rather than orexin or opioid signaling 58 .…”
Section: Discussionmentioning
confidence: 98%
“…Methylphenidate also has a positive dopaminergic effect 1,2 . Dysfunction in the cholinergic-dopaminergic reward system due to hyperghrelinemia is associated with addictive behaviors like compulsive overeating, alcohol use disorder and binge eating whether or not related to bulimia 29,57 .Ghrelin promotes the rewarding, hedonic aspects of eating independent from eating associated with body weight homeostasis 54 . Ghrelin activity is associated with activity or the hippocampus and nucleus accumbens (NA).…”
Section: Discussionmentioning
confidence: 99%